2016
DOI: 10.1111/apps.12078
|View full text |Cite
|
Sign up to set email alerts
|

Cross‐Cultural Differences in Applicant Faking on Personality Tests: A 43‐Nation Study

Abstract: In a globalised world, more and more organisations have to select from pools of applicants from different cultures, often by using personality tests. If applicants from different cultures were to differ in the amount of faking on personality tests, this could threaten their validity: Applicants who engage in faking will have an advantage, and will put those who do not fake at a disadvantage. This is the first study to systematically examine and explain cross‐cultural differences in actual faking behavior. In N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
39
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(41 citation statements)
references
References 148 publications
(282 reference statements)
1
39
1
Order By: Relevance
“…Although these two studies went beyond the previous attempts to describe cross‐cultural differences in faking, there are several reasons why generalising to our context of academic faking is difficult and why a new study is needed. First, although the samples of the previous studies sound large (3,678 in Fell & König; 3,252 in Fell et al, ), they only equate to between 67 and 97 people per country in Fell and König () and between 101 and 110 people per country in Fell et al (). Moreover, the data from both studies came from international market research firms.…”
Section: Theoretical Backgroundmentioning
confidence: 96%
See 3 more Smart Citations
“…Although these two studies went beyond the previous attempts to describe cross‐cultural differences in faking, there are several reasons why generalising to our context of academic faking is difficult and why a new study is needed. First, although the samples of the previous studies sound large (3,678 in Fell & König; 3,252 in Fell et al, ), they only equate to between 67 and 97 people per country in Fell and König () and between 101 and 110 people per country in Fell et al (). Moreover, the data from both studies came from international market research firms.…”
Section: Theoretical Backgroundmentioning
confidence: 96%
“…They found that positive attitudes towards applicant faking in interviews at the country level were negatively related to two cultural GLOBE dimensions (i.e., cultural uncertainty avoidance and gender egalitarianism) and positively related to the GLOBE dimensions of power distance, in‐group collectivism, and humane orientation. In a follow‐up study with 3,678 employees from 43 countries (Fell & König, ), the authors used a standard design for studying applicants’ faking on personality tests by comparing participants’ scores on a Big Five personality test within a hypothetical applicant situation (“faking condition”) with scores on the same Big Five measure within an honest condition (in which participants were instructed to respond honestly). They found systematic country‐level correlations with an overlapping set of cultural practices (i.e., GLOBE's uncertainty avoidance, future orientation, and in‐group collectivism).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 2 more Smart Citations
“…This definition is a slightly simplified version of typical faking definitions. For example, Fell and König () define faking as “applicants’ conscious distortion of responses in order to achieve better scores (e.g., on a personality test) and to increase their chances of being hired” (p. 672; for similar definitions see, e.g., McFarland & Ryan, ; Roulin & Krings, ). Such a simplification is necessary because typical faking definitions only capture faking in self‐reports and not faking in other‐reports.…”
Section: Introductionmentioning
confidence: 99%